Do personality traits and shopping motivations affect social commerce adoption intentions? Evidence from an emerging market - Aydın, Gökhan (Taylor & Francis, 2019)
Social commerce has become a hot topic since the beginning of Web 2.0 era; however, relevant research is scarce in emerging economies. This study aims to fill this research gap and answer the main research question of ?what type of relevant personality traits and shopping motivations affect social commerce adoption intentions?. The research model was developed upon personality traits (openness to experience, need for uniqueness and buying impulsiveness) that are deemed to be relevant to online shopping and social media use. An online questionnaire was conducted on social media users. A total of 269 valid questionnaires were analyzed via structural equation modeling to test for the proposed relationships, majority of which emerged as non-linear. The findings highlight the significance of socialization motives in addition to utilitarian and hedonic shopping motives on social commerce adoption intentions. Openness to experience emerged as a significant trait that has an indirect effect on social commerce adoption intentions. Age and education materialized as significant demographics influencing shopping motivations in a social commerce setting.
Keywords: Buying Impulsiveness; E-Commerce; Need For Uniqueness; Online Shopping; Personality Traits; Social Commerce; Social Media; Socialization; Social Shopping; S-Commerce